The Effectiveness of 0.2% Chlorhexidine Gel on Early Wound Healing after Tooth Extraction: A Randomized Controlled Trial - Amaliya, Amaliya; Ramadhanti, Rika; Hadikrishna, Indra; Maulina, Tantry (European Journal of Dentistry, 2022)
Objective This study aimed to evaluate the effect of 0.2% chlorhexidine (CHX) gel on wound healing after tooth extraction.Materials and Methods A single blind, randomized controlled trial was performed recruiting 32 participants who underwent dental extractions. Patients were randomly allocated for CHX group or placebo group. The primary outcomes were wound closure measured with calipers and healings were assessed by Landry et al index after 7 days of topical application of allocated gels on extraction sites.Results The wound closures were greater in CHX group compared with placebo group and healing scores were correlated with the use of CHX gel (p-value < 0.05).Conclusion In a population of healthy nonsmoker adults, application of 0.2% CHX gel twice a day for 7 days after tooth extraction has a beneficial effect on wound healing.
Keywords: chlorhexidine gel; wound healing; tooth extraction